Optimizing Change Management Using the Analytical Hierarchy Process Method: Analysis with Super Decisions Software - Ken Putri, Lulasnov Viola Prameswari; Mahdiana, Deni (Institut Teknologi dan Bisnis Bina Sarana Global, 2024)
A major challenge in change management lies in selecting unbiased policy alternatives that promote effective decision-making. To overcome this obstacle, this research utilizes Super Decisions software to perform AHP calculations and assess various change management policies. The methodology used includes identifying key criteria affecting change management, structuring the problem into an AHP hierarchy, collecting data through expert surveys or interviews, and analyzing the data using Super Decisions software to determine the criteria weights and optimal policy alternatives. The study revealed that improving Standard Operating Procedures (SOPs) emerged as the most optimal policy alternative. The implementation of AHP demonstrated its ability to provide a systematic and unbiased framework, assisting top management in strategic decision-making. Overall, this study underscores the value of AHP in reducing bias and informing sound change management policies. The study recommends continued adoption and adjustment of the AHP method to suit organizational needs.